Structural and magnetic properties of Cd-Ni spinel ferrites: density functional theory calculations and high-temperature series expansions. (1st November 2020) - Azouaoui, A.; Benzakour, N.; Hourmatallah, A.; Bouslykhane, K.
ABSTRACT: First-principles calculations of density functional theory (DFT) using the generalized gradient approximation (GGA) and generalized gradient approximation with the Hubbard U (GGA + U) for the exchange-correlation energy functional are used to investigate the structural, electronic, and magnetic properties of the spinel system C d x N i 1 − x F e 2 O 4 in the range 0 ≤ x ≤ 1 . High-temperature series expansions (HTSE) combined with the Padé approximants (PA) method and mean field theory (MFT) are applied to the C d x N i 1 − x F e 2 O 4 systems. The lattice parameter and magnetic moment of Fe and Ni ions increase when Cd content x increases. Density of States (DOS) calculations show that the C d x N i 1 − x F e 2 O 4 has a semiconductor behaviour. The obtained theoretical results show that the Curie temperature decreases with x . These obtained results are in agreement with experimental ones.